HUBUNGAN EATING DISORDER, TINGKAT STRESS, DAN KONDISI SOSIAL EKONOMI DENGAN KEJADIAN MALNUTRISI PADA REMAJA KOTA BEKASI - Satriyo Wildan Rahmanto (2023)
Adolescents according to WHO are the population in the age range of 10 - 19 years. West Java Province is one of the provinces where the prevalence of malnutrition exceeds the national prevalence. Recorded in West Java provincial health data, 28.1% of adolescents in West Java province were on malnutrition condition. The incidence of malnutrition can be influenced by internal and external factors such as eating disorder conditions, stress levels, and socioeconomic conditions. This study purpose was to analyze the relationship between eating disorders, stress levels, and socioeconomic conditions on the incidence of malnutrition among high school adolescents in Bekasi City. The study population was 2156 adolescents aged 15-17 years. The sampling technique used was purposive sampling. The research samplel was 165 respondents. The instruments used were respondent characteristics and observation questionnaires, EAT-26 questionnaires, DASS questionnaires, socioeconomic questionnaires including pocket money, parents' latest education, and parents' income. Data analized using chi square showed no relationship between nutritional status variabels and independent variabels except parental income. The relationship value of each variabel respectively with malnutrition (eating disorder P-value = 0.481; stress level P-value = 0.655; pocket money P-value = 0.337; parents' last education P-value = 0.916; parents' income P-value = 0.029).